On the solubility of gases in liquid casting alloys - E. I. Marukovich; V. Yu. Stetsenko; A. V. Stetsenko (Литьë и металлургия, 2023)
It has been shown that hydrogen and oxygen atoms cannot be present in the open pores of crystal lattices of base metals of casting alloys. The solubility of gases in liquid casting alloys is a nanostructured process. Hydrogen and oxygen atoms in melts are adsorbed by basic metal elemental nanocrystals. Nitrogen dissolves in liquid iron, nickel and chromium not in atomic form, but in the composition of elementary nanocrystals and nitride molecules. After deoxidation of molten casting alloys, the main gas dissolved in them is hydrogen.